2001
DOI: 10.1128/mcb.21.13.4413-4424.2001
|View full text |Cite
|
Sign up to set email alerts
|

Human Pex19p Binds Peroxisomal Integral Membrane Proteins at Regions Distinct from Their Sorting Sequences

Abstract: The molecular machinery underlying peroxisomal membrane biogenesis is not well understood. The observation that cells deficient in the peroxins Pex3p, Pex16p, and Pex19p lack peroxisomal membrane structures suggests that these molecules are involved in the initial stages of peroxisomal membrane formation. Pex19p, a predominantly cytosolic protein that can be farnesylated, binds multiple peroxisomal integral membrane proteins, and it has been suggested that it functions as a soluble receptor for the targeting o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
177
1

Year Published

2002
2002
2006
2006

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 125 publications
(196 citation statements)
references
References 37 publications
(63 reference statements)
16
177
1
Order By: Relevance
“…This result also demonstrated the occurrence of multiple binding sites in at least some PMPs as reported previously for mammalian Pmp34p and Pmp22p (Jones et al, 2001;Brosius et al, 2002). The only Pex19p-binding site in higher eukaryotes that has been characterized in detail so far is that of Homo sapiens Pex13p (Fransen et al, 2001). Aligning the Pex13p protein sequences from several species revealed that the Pex19p-binding site of S. cerevisiae represents a highly conserved region within the protein.…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…This result also demonstrated the occurrence of multiple binding sites in at least some PMPs as reported previously for mammalian Pmp34p and Pmp22p (Jones et al, 2001;Brosius et al, 2002). The only Pex19p-binding site in higher eukaryotes that has been characterized in detail so far is that of Homo sapiens Pex13p (Fransen et al, 2001). Aligning the Pex13p protein sequences from several species revealed that the Pex19p-binding site of S. cerevisiae represents a highly conserved region within the protein.…”
Section: Discussionmentioning
confidence: 53%
“…Pex19p interacts with multiple PMPs (Gö tte et al, 1998;Sacksteder et al, 2000;Snyder et al, 2000;Fransen et al, 2001); however, precise Pex19p-binding sites have not yet been dissected and the physiological role of these interactions is under debate. We show here for the first time that Pex19p-binding sites represent short sequences that share a common motif and are integral parts of mPTSs and that these sites are required for the targeting of PMPs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations